Penanaman Pohon Bakau Di Pantai Keraya Kecamatan Kumai Kabupaten Kotawaringin Barat Sebagai Bentuk Kepedulian Terhadap Lingkungan Hidup - Wulandari, Lies Tiarini (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2024)
The coastal area is the border area between land and sea. Coastal areas are areas close to the sea characterized by flat areas and sandy soil composed of various kinds of ecosystems such as mangrove trees. The mangrove ecosystem is a community of tropical and sub- tropical coastal vegetation and is able to grow and develop in muddy coastal tidal areas. Mangrove trees have an important role for the environment, especially the life of flora and fauna in areas around the coast. Apart from that, mangrove trees are able to prevent abrasion and function as wave barriers. The area that has mangrove forests and is quite susceptible to abrasion is Keraya Village, Kumai District, West Kotawaringin Regency as a planting location. This activity aims to increase awareness and open insight into the importance of preserving the environment around the coast by planting mangrove trees. Through community service activities, participants can have awareness and are expected to develop a sense of love for the environment.